Heat Pump Use in Rural District Heating Networks in Estonia - Lepiksaar Kertu (Sciendo, 2021)
District heating has proven to be an efficient way of providing space heating and domestic hot water in populated areas. It has also proven to be an excellent way to integrate various renewable energy sources (RES) into the energy system. In Estonia, biomass covers most of the heat demand, but carbon-intensive fuels are still used to cover peaks and lows. Heat pumps can be a good solution for rural areas, as there is usually plenty of land available for heat pump facilities. In addition, heat pumps require low-grade heat sources such as ambient air, groundwater, lakes, rivers, sea, sewage water, and industrial waste heat. One of the downsides of heat pumps is the need for large investments compared to boilers fired by natural gas and biomass, and electric boilers. This study examines the impact of heat pump use on consumer prices for district heating in rural district heating networks in Estonia.